Análisis descriptivo de la miología flexora y extensora del miembro anterior de Polychrus acutirostris (Squamata, Polychrotidae) - Moro, Silvia; Abdala, Virginia (Papéis Avulsos de Zoologia, 2004)
The musculature of the forelimb of Polychrus acutirostris is described. The anatomy of the flexor and extensor muscles was analyzed, with a record of the sites of origin and insertion and main characteristics for each muscle. The main purposes of this work are: to contribute to the identification of the muscular complexes of the forearm and manus; to update the nomenclature of certain complicated muscles; and to present a model of the forelimb musculature of an arboreal lizard, to allow comparisons with the muscular anatomy of lizards with other locomotor habits.